Achievement Motivation Levels and Their Relationship with Social Cohesion among Basketball Students at the College of Sports Sciences - Alkhraishah, Lama Mamdouh (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to explore the level of achievement motivation and its relationship with social cohesion among basketball students at the College of Sports Sciences. The researcher employed a descriptive approach, suitable for the nature and objectives of the study. The study sample comprised 55 randomly selected male and female students enrolled in the basketball course at the College of Sports Sciences. Data were collected using a researcher-designed questionnaire consisting of 30 items distributed across two domains. The researcher utilized statistical packages for social sciences (SPSS) to obtain the means and standard deviations for all study variables, Cronbach's Alpha for reliability, and the t-test. The results indicated a high level of achievement motivation among basketball students, with an elevated level of social cohesion. Additionally, a significantly positive relationship was found between achievement motivation and social cohesion, with a Pearson correlation coefficient of (0.771). The researcher recommends focusing on enhancing achievement motivation, motivating students to acquire new skills that contribute to their improvement, activating the role of the community to increase social sports cohesion, and enhancing the relationship between motivation and social cohesion among students.
Keywords: Achievement Motivation; Social Cohesion; Basketball